2020
DOI: 10.21077/ijf.2020.67.4.95063-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silkworm (Bombyx mori) pupae on the growth and maturation of Rainbow shark Epalzeorhynchos frenatum (Fowler, 1934) under captive rearing

Abstract: The aim of this study was to determine the impact of replacing fishmeal with silkworm pupae (Bombyx mori) meal in the diet of rainbow shark Epalzeorhynchos frenatum (Fowler, 1934), on growth and maturation. Four isonitrogenous and isocalorific experimental diets (35% CP) were prepared using silkworm pupae (SWP) replacing fish meal at three different levels viz., 30% (T1), 40% (T2) and 50% (T3) and diet with only fish meal served as control (C). The experimental trail was conducted in hapas, in duplicates, inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Insect meal, particularly silkworm meal, has been demonstrated to have immune-modulatory and physiological effects in aquatic species, making it a functional element capable of increasing immune-stimulatory effects in a variety of aquatic animals (The protein of silkworm pupae is high in phenylalanine, methionine, and valine, three important amino acids [122]. Silk worm meal, an insect-based diet, can be used in place of fish meal to enhance the biochemical composition and growth performance of Catla-rohu hybrids [123].…”
Section: Insect Meal-based Bioactive Feed Ingredientsmentioning
confidence: 99%
“…Insect meal, particularly silkworm meal, has been demonstrated to have immune-modulatory and physiological effects in aquatic species, making it a functional element capable of increasing immune-stimulatory effects in a variety of aquatic animals (The protein of silkworm pupae is high in phenylalanine, methionine, and valine, three important amino acids [122]. Silk worm meal, an insect-based diet, can be used in place of fish meal to enhance the biochemical composition and growth performance of Catla-rohu hybrids [123].…”
Section: Insect Meal-based Bioactive Feed Ingredientsmentioning
confidence: 99%
“…SWP meal was found to be an advantageous sustainable feed element in carp diets, with benefits for boosting growth performance and specific physiological markers, according to an eleven-week feeding research on Cyprinus carpio [259]. In the rainbow shark (Epalzeorhynchos frenatum), feeding experiments revealed that SPM could substitute up to 30% of FM in the diet [260].…”
Section: Silkwormmentioning
confidence: 99%
“…Therefore, a better way to mitigate the negative environmental impact of the silk industry is to use these precious resources for feeding poultry and farm animals. Due to their high nutritional content, silk pupae have been used as a possible feed source for livestock and poultry [60,62,90]. This paper examines how silkworm pupae are used as a substitute protein source for cattle and poultry feed, to improve productivity and reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%